#TITLE_ALTERNATIVE# - HAYANI (NIM 10107081); Pembimbing : Dr. Agus Yodi Gunawan, NURUL
Water Filtration is a separation process of solid particles from soiled solution by using porous medium. The phenomenon that occurs in filtration process is the existence of solid particles that was filtrated by porous medium and then it contributes to the mass of porous medium solid phase. The amount of solid particle filtrated will affect the quality of the filtrate. The less solid particle contained inside the filtrate the better the filtration process. One of the method used to determine filtrate quality is to calculate the ratio between solid particle volume fraction and porosity of the porous medium. In this final project, we determine the value of ratio between solid particle volume fraction and porosity of pororus medium and also the changes of the porosity value for each level of porous medium and for each time. The model will be studied analitically and numerically. For the numerical approach, Finite element method will be used. Outcome of this final project shows that type of porous medium, velocity of soiled solution stream, thickness of porous medium, and turbidity level of the soiled solution effect the quality of the filtration result.